Characteristics and capabilities of the hyperspectral imaging microscope. - Huebschman, M.L.
Single-pass multispectral imaging enables applications ranging from whole-chromosome painting to gene mapping. We have developed a prototype Hyperspectral Imaging Microscope (HIM) Workstation to take advantage of multispectral imaging analysis on a single pass. We trade a full specimen image on a single pass for a full emission spectrum on a single pass. The prototype HI microscope collects the visible emission spectrum from a microscope slide by multiple exposures of the CCD camera as it steps across the slide. On each step, one dimension is space and the other is wavelength. The software correlates spatial and spectral information with minimal or no use of optical filters, offering important advantages over a standard epi-fluorescence microscope.
Keywords: CCD camera; Biophysical research technique; Cellular mRNA; Clinical cytogenetics; Fluorescent analysis; Fluorochromes; Full specimen image; Gene mapping; Hyperspectral imaging microscope; Immunophenotyping; Information correlation; Microscope slide; Optical filters; Single-pass multispectral imaging; Spatial information; Spectral information; Standard epifluorescence microscope; Visible emission spectrum